Influence of surface and cloth characteristics on mechanical removal of meticillin-resistant Staphylococcus aureus (MRSA) attached to inanimate environmental surfaces in hospital and healthcare facilities - Mafu, Akier Assanta; Massicotte, Richard; Pichette, Gilbert; Lafleur, Sonia; Lemay, Marie-Josee; Ahmad, Darakhshan (International Journal of Infection Control, 2013)
In health care facilities, the inanimate surface environment can become contaminated with nosocomial pathogen agents. Cleaning has already been accepted as an important factor for controlling the contaminants. For instant, cotton cloths and microfiber may help in the removal of soils and attached bacterial cells. It is also important to know if the nature of the surface can affect the cleaning when we use both microfiber and cotton cloths. In this work, the role of physicochemical factors on bacterial adhesion to stainless steel, melamine and Formica laminate was investigated by assessing the contact angle. In addition, the attachment capability of methicillin-resistant Staphylococcus aureus (MRSA) to the surfaces was studied using scanning electron microscopy technique. The results revealed that, with the exception of Formica laminate, MRSA cells could attach to stainless steel and melamine surfaces after short contact time of 24 h. The outcome also indicated that the microfiber cloths are, slightly, more efficient for removal of soil and microbial cells compared to the cotton cloths. For the surfaces without soils, no significant difference was found when cotton cloths or microfiber cloths were used. It was also appeared, regardless of the type of cloth and presence of soil, the melamine surfaces are the most difficult one to clean.